POTENSI CENDAWAN Synnematium sp. SEBAGAI AGENS PENGENDALI Lawana sp. (FLATIDAE; HOMOPTERA) - ELLYDA ABAS WIKARDI; GNR PURNAYASA; SISWANTO SISWANTO (Jurnal Penelitian Tanaman Industri, 2001)
Potency of Synnematium sp. as biocontrol agent of Lawana sp. (Flatidae; Homoptera)Research on potency of Synnematium sp. as biocontrol agent of Lawana sp. was carried out from May to June 2001 with a scries of pathogenicity tests in ield laboratory Narmada (Mataram) and Insect Laboratory Balittro, Bogor. The research consisted of two pats ie: (I) inoculation of the fungi on egg cluster of Lawana sp. of different ages, and (2) inoculation of the fungi with various application methods to the imagoes of Lawana sp.. Results showed that Synnematium sp. could infect 0-4 days old of eggs. Eggs more Uian 4 days old could be also infected, however 3-5% could still hatch to be nymphs. Application to parasitized eggs did not affect the parasitoid to hatch. Tests on the adults showed that 3 days ater inoculation with the fungi, adults of Lawana sp. became weak, while the motality occurred ater 5 days inoculation. Colony of Synnematium sp. on PDA media, primarily was white, then dark small balls sclcrotium, and formed synnemata on the top. The presence of sclerotia and synnemata seemed that the fungi is potential to be developed as microbial insecticide material ("micoinsectiside").